2015
DOI: 10.1093/abbs/gmv050
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-related alterations in gene expression patterns in the developing murine hippocampus

Abstract: It is well known that consuming alcohol prior to and during pregnancy can cause harm to the developing fetus. Fetal alcohol spectrum disorder is a term commonly used to describe a range of disabilities that may arise from prenatal alcohol exposure such as fetal alcohol syndrome, partial fetal alcohol syndrome, alcohol-related neurodevelopmental disorders, and alcohol-related birth defects. Here, we report that maternal binge alcohol consumption alters several important genes that are involved in nervous system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…In an ethanol exposure paradigm similar to the one used in this study in which rats were exposed to intermittent ethanol and their prefrontal cortex was analyzed 21 days after the last exposure, ion channels, including those that influence neurotransmitter release through effects on membrane potentials and calcium flux, emerged as one of the top GO categories in a miRNA and a DNA methylation study (Tapocik et al, 2013; Barbier et al, 2015). Calcium signaling also emerged as an important pathway following maternal binge-like ethanol doses in embryonic day 18 fetuses in a microarray study (Mandal et al, 2015b). Our results therefore further indicate an important role for calcium signaling in AUD, and suggest epigenetic mechanisms may encode persisting alterations in this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In an ethanol exposure paradigm similar to the one used in this study in which rats were exposed to intermittent ethanol and their prefrontal cortex was analyzed 21 days after the last exposure, ion channels, including those that influence neurotransmitter release through effects on membrane potentials and calcium flux, emerged as one of the top GO categories in a miRNA and a DNA methylation study (Tapocik et al, 2013; Barbier et al, 2015). Calcium signaling also emerged as an important pathway following maternal binge-like ethanol doses in embryonic day 18 fetuses in a microarray study (Mandal et al, 2015b). Our results therefore further indicate an important role for calcium signaling in AUD, and suggest epigenetic mechanisms may encode persisting alterations in this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When the control group brain size was normalized to a value of 100, the relative values in the ethanol-treated group for diameters a and b were 92.44 and 94.36, respectively. This result clearly indicates that a binge level of ethanol treatment during the synaptogenesis period evoked smaller brain volume, as did ethanol treatment during neurogenesis (Mandal et al, 2015).…”
Section: Resultsmentioning
confidence: 72%
“…Mouse and rat studies showed the association between prenatal ethanol exposure and gene expression changes in postnatal and adult stages [34][35][36][37] . This study examined ethanol-induced gene expression changes during embryogenesis before gastrulation.…”
Section: Discussionmentioning
confidence: 99%